Risk factors for complications after breast reduction surgery. Issue 1 (February 2014) - Lewin, Richard; Göransson, Marie; Elander, Anna; Thorarinsson, Andri; Lundberg, Jonas; Lidén, Mattias
Abstract Women who suffer from breast hypertrophy commonly have physical symptoms such as back pain and psychosocial problems. Breast reduction surgery is performed to relieve these problems. Side-effects must be kept to a minimum. Risk factors for developing postoperative complications have not clearly been identified so far. The aim of this study was to identify risk factors that lead to complications. The medical records of 512 consecutive women (mean age 40 years) who underwent bilateral breast reduction were retrospectively studied. All complications that occurred during the first 30 days after the operation were retrieved from medical records. Complications occurred in 32% of the patients within 30 days of surgery. The most common complication was infection at the surgical site (16%) followed by delayed wound healing (10%). Fat necrosis occurred in 2.5%, partial areola necrosis in 3.1%, and total areola necrosis in 0.6% of the patients. A longer suprasternal notch to nipple distance gave significantly higher risk of postoperative infection (p < 0.001) and necrosis in the mammilla (p < 0.001). The resected specimen weight during the operation was found to significantly influence the risk of delayed wound healing (p = 0.021) and fat necrosis (p < 0.001). Smokers had twice the risk of getting a postoperative infection, RR = 2.0 (95% CI = 1.3–3.1). Diabetics had a significantly higher risk of necrosis of the areola (p = 0.003). All the above predictors were identified as independent predictors. Complications after breast reduction are common. The study has identified several risk factors for complications, some of them independent, which might be avoidable by performing a careful preoperative evaluation of the patient.